Production scheduling system for job shop enterprise using ANT colony optimization approach - Ho, Fu Haw (2008)
Current computerized scheduling system shows inability to search for the best product route among all possible routes. But in the real working environment, different product route plays a vital role especially for enterprises that produces a variety of product at one time. This project describes the development of a scheduling system that generates all possible product route. This scheduling system operate based on the push scheduling concept. Then, with the aid of Ant Colony Optimization concept, all possible product processing routes are evaluated according to the total product scheduling time. At the end of the optimization process, the best product processing route can be identified based on the shortest processing time (SPT) calculated in the scheduling system. The system was developed using the Microsoft Visual Basic 6.0, while the system databases were built using the Microsoft Access. All the required data are provided by a manufacturing company in Muar, Johor. Results shows that the proposed product processing route is better than the generated default scheduling in terms of the total processing time and shortest machines idleness in all the workstations.